The complete book of Yiquan - Tang, C. S. (Singing Dragon, 2015)
The first complete guide to the rarely taught martial art, Yiquan, still shrouded in mystery. With clear photographs and explanations, this comprehensive illustrated book fully describes the postures and movements of Yiquan and provides information on Yiquan's origin, weapons, programs, grading, and more.